IMPLEMENTATION OF SCIENTIFIC APPROACHES IN THEMATIC LEARNING IN CLASS IVA MADRASAH IBTIDAIYAH NEGERI II MODEL PALEMBANG - Faisal Faisal; Yulita Yulita; Tastin Tastin (Fakultas Tarbiyah, IAIN Fattahul Muluk Papua, 2022)
The scientific approach is a learning process designed so that students actively construct concepts, laws, or principles through observing, asking, reasoning, trying, and communicating. The implementation of thematic learning with a scientific approach at the elementary school level is an educational program in the 2013 curriculum. The application of thematic learning with a scientific approach is important because, based on the 2013 curriculum, meaningful learning can occur by actively engaging students in learning activities through observing, asking to reason, trying and communicating. This study aims to describe and analyze (1) the implementation of the scientific approach in thematic learning, (2) the constraints faced in applying a competitive approach to thematic learning, and (3) efforts made to overcome the obstacles faced in applying the scientific approach to learning thematic. The type of research used is qualitative research. The method of collecting data uses the method of observation, interviews, and documentation. The data analysis used in this study is according to Mattew B. Miles and Michael Huberman, which includes data reduction, data display, and conclusion. The results showed that the implementation of the scientific approach in Class IVA MIN II Palembang in thematic learning had gone well seen from the aspect of observing, asking, reasoning, trying, and communicating. The constraints faced when implementing a scientific approach are still lack of teacher preparation in learning activities, too short time, and lack of courage of students in expressing their opinions. Efforts made to overcome the obstacles faced are by building teacher working groups to overcome the lack of teacher preparation in learning activities and provide motivation to students to encourage students to be more active in learning activities.